Windows 3.0 : a definitive guide for DOS users - Vose, Michael (Reading, Massachusetts : Addision-Wesley Publishing Company, 1990)
Windows 3.0: A Definitive Guide for DOS Users approaches Windows from the perspective of the DOS user. It is both a tutorial and a reference manual. Step-by-step instructions take new Windows users through many important tasks, including installation and setup, running applications, printing, copying and much more. Carefully placed charts and graphics help the more advanced quickly become power users. Experienced DOS users will benefit from useful comparisons between DOS and Windows.
Part One. Windows-A Super Shell for DOS -- Part Two. A DOS User's Survival Guide
Includes index.
Keywords: MICROSOFT WINDOWS (COMPUTER FILE)